Large-Scale Agricultural Investments under Poor Land Governance Systems: Actors and Institutions in the Case of Zambia - Kerstin Nolte (German Institute of Global and Area Studies (GIGA), 2013)
This paper reveals how the outcomes of large-scale land acquisitions made by foreign investors in Zambia are determined by the characteristics of the country's land governance system. Proposing a conceptual framework adapted from Williamson (1998), and using evidence constituted by expert interviews and focus group discussions, we scrutinize the nature and evolution of the Zambian land governance system, the steps that an investor has to go through in order to attain land and the actors shaping the acquisition process. Shedding light on the acquisition process for land, we find that enforcement of formal rules is currently weak. Depending on how the actors play the game, land acquisitions can feature aspects of both land grabs and of development opportunities. If customary land is targeted, consultation, displacements and compensations become especially problematic issues. Moreover, we find that the power balance between actors has been altered by the presence of these investors. In particular, local authorities have gained greater power and influence.
Keywords: K42; O13; O17; P48; Q15; 300; large-scale land acquisitions; Zambia; land governance; institutions; land grab